Anti-silencing factor 1A is associated with genome stability maintenance of mouse preimplantation embryos. Issue 4 (9th January 2020) - Deng, Kai; Feng, Wanyou; Liu, Xiaohua; Su, Xiaoping; Zuo, Erwei; Du, Shanshan; Huang, Yongjun; Shi, Deshun; Lu, Fenghua
Abstract: Genome stability is critical for the normal development of preimplantation embryos, as DNA damages may result in mutation and even embryo lethality. Anti-silencing factor 1A (ASF1A) is a histone chaperone and enriched in the MII oocytes as a maternal factor, which may be associated with the maintenance of genome stability. Thus, this study was undertaken to explore the role of ASF1A in maintaining the genome stability of early mouse embryos. The ASF1A expressed in the preimplantation embryos and displayed a dynamic pattern throughout the early embryonic development. Inhibition of ASF1A expression decreased embryonic development and increased DNA damages. Overexpression of ASF1A improved the developmental potential and decreased DNA damages. When 293T cells that had been integrated with RGS-NHEJ were co-transfected with plasmids of pcDNA3.1-ASF1A, gRNA-NHEJ, and hCas9, less cells expressed eGFP, indicating that non-homologous end joining was reduced by ASF1A. When 293T cells were co-transfected with plasmids of HR-donor, gRNA-HR, hCas9, and pcDNA3.1-ASF1A, more cells expressed eGFP, indicating that homologous recombination (HR) was enhanced by ASF1A. These results indicate that ASF1A may be associated with the genome stability maintenance of early mouse embryos and this action may be mediated by promoting DNA damage repair through HR pathway. Abstract : Anti-silencing factor 1A was expressed in mouse early embryos, and played an important role in maintaining genome stability.